The Impact of Subjectivity on Financial Accounting - Papadeas, Panagiotis (International Conference on Business and Economics - Hellenic Open University, 2023)
In this paper it is attempted to explore current trends in Financial Accounting, that connect research endeavors in the relatively new branch of Behavioral Finance, with the impact of subjectivity on the accounting cycle of each fiscal year, as well as on the preparation of financial statements. The investigation of subjective factors in Financial Accounting expands its scope, while the systematic utilization of its two-way relationship with the field of Neurofinance (unbiased data) may create a broader framework of knowledge for the further improvement of the investment process, through an understanding of the methodology required by accounting operations and rules up until the preparation of financial statements. By extension, a better understanding of how financial markets operate will be beneficial not only for governments wishing to promote savings incentives and responsible management, but also for supervisory authorities seeking to ensure that the market for personal financial services operates rationally and without bias. Keywords: Behavioral Finance, Neurofinance, Financial Accounting JEL Classification: D87, G41, M41